No todos «por la Patria». Deserciones y problemas logísticos en el ejército durante la independencia peruana, 1820-1822 - Alvarado Luna, Patricio A. (2023)
The news of the proximity of the Liberating Expedition and the subsequent presence of José de San Martín’s army in the Viceroyalty of Peru generated a series of desertions within the royalist army, both among the high command and among the common troops. We will analyze the measures used by both the viceregal government and the Liberation Army between 1820 and 1822 to solve logistical problems and, especially, to stop desertions. Moreover, the study will be emphasized on the possible reasons why this situation occurred. Likewise, the measures and sanctions taken against these deserters and the effects that this had on the morale of each army will be explained.